Pemberdayaan Pendekatan Pendidikan Jalur Sekolah dan Luar Sekolah - Maman Rachman (Universitas Negeri Malang, 2016)
This qualitative study was an attempt to identify the problems impeding the implementation of educational approach and to look for suggestions to enlighten and empower approaches to two subsystems of education. Data were collected by in-depth interview and observation in Semarang Municipality. The results show that the system, curriculum, means, learning-teaching strategy, and environment are the crucial factors in the educational management. The suggestions offered are that institutional cooperation is needed, an integrated approach involving the school and out of school education institutions must be enhanced, network of information have to be intertwined, and the Ki Hadjar Dewantara's approach model ought to be socialized and disseminated to all of the two fields of education